Plasma Adiponectin and Its Correlation with Carotid Intima-Media Thickness in Obesity and in Type 2 Diabetes and Nonalcoholic Fatty Liver Disease - Maha Hussein; Aasem Saif; Mona Amin; Osama Khalafallah; Ahmed Hussien; Samar Aboulsoud; Shrook Mousa (Journal of Nutrition and Metabolism)
Background and Aim. Low plasma adiponectin has been found in both obese subjects and patients with type 2 diabetes mellitus (T2DM). Also, it was reported in patients with nonalcoholic fatty liver disease (NAFLD). We assessed plasma adiponectin and its correlation with carotid intima-media thickness (CIMT), as a marker of atherosclerosis, in Egyptian patients with NAFLD. Methods and Results. The study included 200 Egyptian subjects. They were divided into four equal groups: group 1: obese patients with NAFLD and T2DM (O+/NAFLD+/DM+), group 2: nonobese patients with NAFLD and T2DM (O-/NAFLD+/DM+), group 3: obese nondiabetic patients with NAFLD (O+/NAFLD+/DM-), and group 4: nonobese healthy control subjects. Plasma adiponectin was measured using ELISA (enzyme-linked immunosorbent assay) technique. Ultrasonography was used to diagnose NAFLD. CIMT was assessed using Doppler ultrasonography. Plasma adiponectin was significantly lower and CIMT was significantly higher in O+/NAFLD+/DM+, as compared with O-/NAFLD+/DM+, O+/NAFLD+/DM-, and control subjects (p<0.001 for all). A significant negative correlation was found between adiponectin and CIMT in obese patients with NAFLD (p<0.05), but not in patients with NAFLD and T2DM. The significant independent predictors of CIMT were diabetes duration, BMI (body mass index), albumin/creatinine ratio, and cholesterol. Conclusion. Plasma adiponectin is inversely correlated with CIMT in obese patients with NAFLD, but not in patients with NAFLD and T2DM. Hypoadiponectinemia could be a good indicator of cardiovascular risk in obese patients with NAFLD, with or without T2DM, but not in nonobese patients with NAFLD.